Physical and psychological determinants of diabetes associated depression among patients receiving oral hypoglycemic agents a versus insulin regimen - Dr .V.KRISHNAN; Dr .R.KANNAN (International Journal of Pharma and Bio Sciences, 2016)
Study was cocuted to assess the physical and psychological determinants of diabetes associated depression with respect to their medication It was a Observational , Cross sectional survey was done using patient health questionnaire (PHQ-9 ) under ICMR-STS scheme to screen for depression assessment among patients of type diabetes mellitus receiving oral hypoglycaemic agents with or without insulin injection . Self prepared and validated questionnaire was used to know the psychological determinants and misconnects of diabetes among our patients. Our study results showed physical determinants including female sex {( P<0.05 ) PHQ 9 ( 9.12 ) }, higher glycoslated hemoglobin values {( P<0.05 ) ( PHQ9- 9.61 }and co morbidity{( P <0.001) ( PHQ9 – 10.79 )} is significantly associated with depression among diabetic population. Psychological determinants includes initiation of insulin, fear of self injection which is seen among 35.8 % of insulin takers with PHQ-9 score of 9.81 and our study showed only less number diabetes patients uses less painless insulin delivering devices (15.7%) and diabetes education available to very few patients ( 13.6%). Diabetes education, screening for unsaid depression, development of cost effective and painless insulin delivery devices is still under achieved goal of diabetes management.